ONC206, an Imipridone Derivative, Induces Cell Death Through Activation of the Integrated Stress Response in Serous Endometrial Cancer In Vitro - Zhang, Yingao; Huang, Yu; Yin, Yajie; Fan, Yali; Sun, Wenchuan; Zhao, Xiaoling; Tucker, Katherine; Staley, Allison; Paraghamian, Sarah; Hawkins, Gabrielle; Prabhu, Varun; Allen, Joshua E.; et al. (Frontiers in Oncology, 2020)
ONC206 (Oncoceutics) is an imipiridone with nanomolar potency and analogue of ONC201, a selective dopamine receptor D2 (DRD2) antagonist currently being investigated in phase II clinical trials for serous endometrial cancer (SEC). This study investigated the anti-proliferative efficacy of ONC206 in SEC cell lines as well as its impact on cellular stress and adhesion/invasion. ONC206 inhibited cellular proliferation in a dose-dependent manner and was more potent than ONC201 in the ARK1 (IC50=0.33µM vs IC50=1.59uM) and SPEC-2 (IC50=0.24uM vs IC50=0.81uM) cell lines. Treatment with ONC206 resulted in induction of ROS production and reduction of mitochondrial membrane potential, accompanied by an increase in cleaved caspase-3 and caspase-9 activity (p<0.01) ONC206 also significantly inhibited cellular adhesion and migration in both cell lines (p<0.01). Pretreatment with the stress inhibitor N-acetylcysteine (NAC) significantly attenuated the efficacy of ONC206 on cell proliferation, ROS production and cellular invasion. ONC206 demonstrates nanomolar potency for the inhibition of proliferation in SEC cells. Specifically, ONC206 utilizes ISR activation as a significant pathway in the propagation of its anti-proliferative and anti-metastatic effects. Thus, ONC206 may be a promising agent in future SEC clinical trials as was its predecessor ONC201.